Exploring Parental Mediation of Internet Use Through Young Children's Perspective - Dulkadir Yaman, Nihal; Yurdakul, Işıl Kabakçı (Springer, 2022)
The purpose of this study was to investigate the parental mediation of children's internet use from middle school students' point of view. In doing so, we first developed a Parental Mediation Scale. Exploratory factor analysis suggested a four-factor structure (monitoring, safety, active, technical mediation), which was then verified through confirmatory factor analysis. After conducting validity and reliability studies of the scale, we applied it to 416 Turkish middle school students in the 2018-2019 school year. To examine the parental mediation of internet use in terms of demographic characteristics, we employed group comparison tests (i.e., independent samples t-Test and one-way ANOVA). The results indicated that middle school students perceived the mediation of their parents at a medium level. Moreover, parental mediation of internet use did not differ based on the age of children, child's level of education, the gender of children, number of children in the family, parents' level of education, and family's income level.
Keywords: Parental mediation scale; Children's internet use; Parental mediation; Scale; Determinants; Adolescents; Guidance; Styles